2023
DOI: 10.1167/tvst.12.2.32
|View full text |Cite
|
Sign up to set email alerts
|

Validation of 16S rRNA Gene Sequencing of the Periocular Microbiome and Lack of Alteration by Topical Eyedrops

Abstract: Purpose Genomic techniques for characterizing the ocular microbiome require further validation. We compared the microbiome of patients’ eyelids through both conventional culture and 16S rRNA analysis and analyzed the impact of eyedrop use on microbiome diversity. Methods Ninety-eight patients followed for management of glaucoma or suspicion of glaucoma had eyelid swabs performed with Isohelix MS Mini DNA Swabs (98 participants) and ESwabs (49 participants) for 16S rRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…One study on the prolonged use of prostaglandin analogs in glaucoma treatment found a stable OSM among participants but lacked a healthy control group for direct comparison [ 59 ]. Similarly, a study comparing eyelid microbiomes in glaucoma patients found no association between microbiome composition and the use of preservative-containing eyedrops [ 60 ]. Furthermore, a study assessing the impact of topical antiglaucomatous eye drops on conjunctival flora in glaucoma patients and healthy controls revealed a significant increase in bacterial isolates in glaucoma patients, particularly Staphylococcus hominis and Candida spp.…”
Section: Discussionmentioning
confidence: 99%
“…One study on the prolonged use of prostaglandin analogs in glaucoma treatment found a stable OSM among participants but lacked a healthy control group for direct comparison [ 59 ]. Similarly, a study comparing eyelid microbiomes in glaucoma patients found no association between microbiome composition and the use of preservative-containing eyedrops [ 60 ]. Furthermore, a study assessing the impact of topical antiglaucomatous eye drops on conjunctival flora in glaucoma patients and healthy controls revealed a significant increase in bacterial isolates in glaucoma patients, particularly Staphylococcus hominis and Candida spp.…”
Section: Discussionmentioning
confidence: 99%
“… 32 Another study found no changes of the eyelid margin microbiome based on eyedrop preservatives. 42 As a result, there are currently few reasons to choose one AT over another comparable formulation. 43 To better understand how the OSM may mediate DES and AT therapy, we conducted this trial comparing the OSM effects of CMC-ATs with a control PEG-AT without CMC.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 52 Although conventional culture can reveal many of the bacterial species present in the OSM, metagenomic analysis has now revealed a community of low-abundance bacteria on the ocular surface which should be accounted for. 33 , 42 The ocular surface has a relatively stable core OSM shared between most individuals, consisting of common genera such as Corynebacterium, Staphylococcus, Streptococcus, Pseudomonas, Acinetobacter, and Propionibacterium . 16 , 53 Less commonly identified genera such as Bacteroides and Neisseria remain present in individuals after serial swabs, potentially representing an individual-specific core OSM as well.…”
Section: Discussionmentioning
confidence: 99%
“…More than 50 genera and several species have been identified via conventional culture and 16S rRNA analysis [18]. Maintaining microbial diversity (defined as the range of different kinds of unicellular organisms, bacteria, archaea, protists, and fungi) on the ocular surface is crucial to maintaining healthy and balanced ocular homeostasis [19].…”
Section: The Ocular Microbiome: Unveiling the Diversity And Dynamics ...mentioning
confidence: 99%